2023
DOI: 10.1111/jocd.15601
|View full text |Cite
|
Sign up to set email alerts
|

Role of HIF‐1α in pathogenic mechanisms of keloids

Abstract: Backgrouds and Objective Keloids are defined as overrepairing products that develop after skin lesions. Keloids are characterized by the proliferation of fibroblasts and the overaccumulation of extracellular matrix components (mainly collagen), leading to a locally hypoxic microenvironment. Hence, this article was aimed to review hypoxia in pathogenesis of keloids. Methods We reviewed and summarized the relevant published studies. Results Hypoxia results in the accumulation of hypoxia‐inducible factor 1α (HIF‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 118 publications
0
3
0
1
Order By: Relevance
“…Previous reports ( Kang et al, 2020 ; Lei et al, 2019 ; Qiu et al, 2023 ; Zhang et al, 2006 ) have suggested that keloid tumors likely exist in a state of relative hypoxia, which is at odds with standard cell culture incubators (ie, 20% oxygen). A high-content screen ( Figure 1 ) that can profile drug effects in tissue conditions (ie, hypoxia) was developed.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous reports ( Kang et al, 2020 ; Lei et al, 2019 ; Qiu et al, 2023 ; Zhang et al, 2006 ) have suggested that keloid tumors likely exist in a state of relative hypoxia, which is at odds with standard cell culture incubators (ie, 20% oxygen). A high-content screen ( Figure 1 ) that can profile drug effects in tissue conditions (ie, hypoxia) was developed.…”
Section: Resultsmentioning
confidence: 96%
“…Furthermore, standard assay conditions such as 20% oxygen may not be consonant with in vivo drug effects because the dermal tissue oxygen concentration is reported to be 1–4% ( Wang et al, 2003 ). Several groups have documented the expression of HIF1-a in human keloidal tissue, suggesting that the in situ ambient oxygen might be even less ( Kang et al, 2020 ; Lei et al, 2019 ; Qiu et al, 2023 ; Zhang et al, 2006 ). Taken together, there is a clear need to devise a screen in tissue conditions using secreted collagen as the phenotypic endpoint and 1% oxygen to hypoxia.…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxia has been shown to promote proliferation and inhibit the apoptosis of KFs via the HIF-1α-dependent mechanism, and these responses could be modulated pharmacologically using resveratrol [63]. Thus, research on the role of HIF-1α in keloid pathogenesis would provide a new opportunity to develop therapeutic approaches [64].…”
Section: Hypoxia-inducible Factor (Hif)-1αmentioning
confidence: 99%
“…Крім того, надекспресія HIF-1 корелює з посиленою експресією профіброзних факторів і надмірною фіброгенною відповіддю, що призводить до розвитку келоїдних і гіпертрофічних рубців [12].…”
Section: матеріали та методи дослідженняunclassified